Prognosis of patients with metastatic renal cell carcinoma and pancreatic metastases. (6th July 2015) - Kalra, Sarathi; Atkinson, Bradley J.; Matrana, Marc Ryan; Matin, Surena F.; Wood, Christopher G.; Karam, Jose A.; Tamboli, Pheroze; Sircar, Kanishka; Rao, Priya; Corn, Paul G.; Tannir, Nizar M.; Jonasch, Eric
Abstract : Objectives: To identify the clinical outcomes of patients with metastatic renal cell carcinoma (mRCC) with pancreatic metastases (PM) treated with either pazopanib or sunitinib and assess whether PM is an independent prognostic variable in the current therapeutic environment. Patients and Methods: A retrospective review of patients with mRCC in an outpatient clinic was carried out for the period January 2006 to November 2011. Patient characteristics, including demographics, laboratory data and outcomes, were analysed. Baseline characteristics were compared using chi‐squared and t ‐tests and overall survival (OS) and cancer‐specific survival (CSS) rates were estimated using Kaplan–Meier methods. Predictors of OS were analysed using Cox regression. Results: A total of 228 patients were reviewed, of whom 44 (19.3%) had PM and 184 (81.7%) had metastases to sites other than the pancreas. The distribution of baseline characteristics was equal in both groups, with the exception of a higher incidence of previous nephrectomy, diabetes and number of metastatic sites in the PM group. Four patients had isolated PM, but the majority of patients (68%) with PM had at least three different organ sites of metastases, as compared with 29% in patients without PM ( P < 0.01). The distribution of organ sites of metastases was similar, excluding the pancreas, in those with and those without PM ( P > 0.05). The median OS was 39 months (95% confidence interval [CI] 24–57, hazard ratio 0.66, 95% CI 0.42–0.94; P = 0.02) for patients with PM, compared with 26 months (95% CI 21–31) for patients without PM ( P < 0.01). CSS was 42 months (95% CI 30–57) in the PM group and 27 months (95% CI 22–33) in the control group ( P = 0.05). Conclusions: Despite a higher number of affected organ sites in the PM cohort, mRCC behaviour in this cohort appears to be more indolent, as demonstrated by a higher median OS. These findings suggest that host or tumour features associated with PM may represent a less aggressive tumour phenotype.